2019
DOI: 10.1136/gutjnl-2018-317632
|View full text |Cite
|
Sign up to set email alerts
|

RSPO2 gene rearrangement: a powerful driver of β-catenin activation in liver tumours

Abstract: ObjectiveWe aimed at the identification of genetic alterations that may functionally substitute for CTNNB1 mutation in ß-catenin-activated hepatocellular adenomas (HCAs) and hepatocellular carcinoma (HCC).DesignLarge cohorts of HCA (n=185) and HCC (n=468) were classified using immunohistochemistry. The mutational status of the CTNNB1 gene was determined in ß-catenin-activated HCA (b-HCA) and HCC with at least moderate nuclear CTNNB1 accumulation. Ultra-deep sequencing was used to characterise CTNNB1wild-type a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 38 publications
1
32
0
1
Order By: Relevance
“…All abnormal transcripts fused RSPO2 exon 2 or 3 to an adjacent RNA transcribed sequence located 58 813–58 922 nucleotides upstream (chr8:108,141,620–108,141,729, hg38) (figure 1B). RSPO2 exon 2 boundaries were similar to that described by Longerich and collaborators,1 whereas the upstream sequence was variable. In two of the tumours with abnormal RSPO2 transcript, we performed whole-genome sequencing and we observed no focal deletions at the DNA level.…”
supporting
confidence: 79%
See 2 more Smart Citations
“…All abnormal transcripts fused RSPO2 exon 2 or 3 to an adjacent RNA transcribed sequence located 58 813–58 922 nucleotides upstream (chr8:108,141,620–108,141,729, hg38) (figure 1B). RSPO2 exon 2 boundaries were similar to that described by Longerich and collaborators,1 whereas the upstream sequence was variable. In two of the tumours with abnormal RSPO2 transcript, we performed whole-genome sequencing and we observed no focal deletions at the DNA level.…”
supporting
confidence: 79%
“…Thomas Longerich and collaborators1 recently published an intriguing observation in hepatocellular adenoma (HCA) showing an activation of the Wnt/ß-catenin signalling pathway without CTNNB1 or APC mutations. The authors identified a recurrent deletion leading to a fusion between a short interspersed nuclear element (SINE) sequence and RSPO2 gene in three HCAs and three hepatocellular carcinomas (HCCs) all activated for ß-catenin, including one tumour with CTNNB1 mutations and five tumours without APC or CTNNB1 mutations.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Such a heterogeneity was already known for IHCAs, in which several genes might be involved, with variable frequencies. Moreover, RSPO2 is shown by Longerich et al 1 to be also involved in a small proportion of hepatocellular carcinomas, which is not surprising in light of the major role played by the Wnt/beta-catenin pathway in liver carcinogenesis. These results reinforce the connections already demonstrated between the b-HCA subgroup and HCC.…”
mentioning
confidence: 85%
“…In Gut , Longerich et al describe the identification of a new gene, RSPO2 , involved in the pathogenesis of hepatocellular adenomas (HCA) and of a small fraction of hepatocellular carcinomas (HCC), through the activation of the Wnt/beta-catenin pathway, already known to be involved in the pathogenesis of a significant proportion of liver tumours 1. These results reduce the percentage of so-called ‘unclassified’ HCA, underline the tight relationship of some HCA with HCC and add another piece to the puzzle of the extraordinary clinical and biological diversity of HCA.…”
mentioning
confidence: 99%